Two new species of Acontias (Acontinae, Scincidae) from the Mpumalanga Highveld escarpment of South Africa - Conradie, Werner; Busschau, Theo; Edwards, Shelley (Zootaxa, 2018)
The African genus of fossorial legless lizards (Acontias Cuvier) currently comprises 26 species and subspecies. In a recent study on the two disjunct populations of Acontias breviceps Essex, the presence of cryptic species was discovered. Here, we increase the sampling size and describe these disjunct populations from the Mpumalanga Escarpment of South Africa as new species. The new species differ from congeners based on a combination of factors, including the number of midbody, ventral, and subcaudal scale counts, ventral pigmentation, allopatric distributions, and genetic divergences. The new species are genetically distant from nominal A. breviceps, with which it shares overall pigmentation and scalation. The new description adds to the growing number of Mpumalanga escarpment endemic reptiles, and highlights the area as a biodiversity hotspot. The use of vertebral counts as a distinguishing character between species is briefly discussed.